2015
DOI: 10.1016/j.jmb.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

The Pentameric Nucleoplasmin Fold Is Present in Drosophila FKBP39 and a Large Number of Chromatin-Related Proteins

Abstract: Nucleoplasmin is a histone chaperone that consists of a pentameric N-terminal domain and an unstructured C-terminal tail. The pentameric core domain, a doughnut-like structure with a central pore, is only found in the nucleoplasmin family. Here, we report the first structure of a nucleoplasmin-like domain (NPL) from the unrelated Drosophila protein, FKBP39, and we present evidence that this protein associates with chromatin. Furthermore, we show that two other chromatin proteins, Arabidopsis thaliana histone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 55 publications
3
35
1
Order By: Relevance
“…Importantly, a range of independent techniques implemented in this study revealed that the Mm of the FKBP39 oligomer corresponds to the theoretical weight of the tetramer. Therefore, our findings stand in opposition to those of a recent structural study on an isolated N-terminal NPL domain18 from D. melanogaster FKBP39, and we report for the first time the quaternary structure of the tetrameric arrangement of the NPL domain in the context of the full-length protein.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Importantly, a range of independent techniques implemented in this study revealed that the Mm of the FKBP39 oligomer corresponds to the theoretical weight of the tetramer. Therefore, our findings stand in opposition to those of a recent structural study on an isolated N-terminal NPL domain18 from D. melanogaster FKBP39, and we report for the first time the quaternary structure of the tetrameric arrangement of the NPL domain in the context of the full-length protein.…”
Section: Discussioncontrasting
confidence: 99%
“…1A, at the FKBP39 N-terminus, the first 86 amino acid residues have a low disorder tendency of approximately 0.25, suggesting the existence of an ordered structure. This prediction is in agreement with the results of a search for conserved domains by Phyre2 software (data not shown) and a recent nuclear magnetic resonance (NMR) structural study of the N-terminal fragment of FKBP39, which also indicated an ordered structure18. Similarly, the C-terminal fragment of FKBP39 between 257 and 357 amino acid residues, excluding a short fragment between residues 321 and 339, did not exhibit a disordered tendency, with a score below 0.5.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Each of these three proteins is conserved throughout vertebrates, while more evolutionarily distant members of the family may be found in invertebrates and in lower eukaryotes (Edlich-Muth et al 2015;Frehlick et al 2007;Gudavicius et al 2014), and all three possess the ability to bind histones, regulate their assembly into nucleosomes and promote their loading onto and/or eviction from DNA, identifying them as true histone chaperones (Frehlick et al 2007;Finn et al 2012). While NPM2 and NPM3 appear in vivo to function exclusively as histone chaperones during both somatic cell growth and, in particular, gametogenesis and fertilization (Finn et al 2012;Okuwaki et al 2012), NPM1 has gained numerous additional functions during evolution and acts in numerous independent cellular pathways.…”
Section: Nucleophosmin and Nucleolin: Two Multifunctional Nucleolar Pmentioning
confidence: 99%